Method for manufacturing a perovskite thin film, perovskite thin film, and photoelectric conversion device including the perovskite thin film
Patent Information
- Application Number
- KR1020250194197
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-12-09
- Publication Date
- 2026-09-04
- Estimated Expiration
- 2045-12-09
Smart Images

Figure 112025139030984-PAT00013_ABST
Abstract
Description
Technology Field
[0001] The embodiments relate to a method for manufacturing a perovskite thin film, a perovskite thin film, and a photoelectric conversion device comprising the perovskite thin film; more specifically, they relate to a method for forming a high-quality perovskite thin film in which compositional uniformity is improved and phase non-uniformity is suppressed by adjusting the composition of a precursor solution. Background Technology
[0002] Recently, research for the development of high-efficiency solar cells has been actively conducted, and tandem solar cells are receiving particular attention as a way to overcome the limitations of a single absorption layer. Tandem solar cells have the advantage of being able to utilize the solar spectrum more efficiently by connecting two or more light-absorbing layers with different band gaps in series.
[0003] Among them, perovskite / silicon tandem solar cells are attracting attention as next-generation high-efficiency solar cells because they can combine the stability of silicon solar cells with the high photoelectric efficiency of perovskite materials.
[0004] Perovskites are widely studied as upper light-absorbing layer materials due to their advantages, such as easy bandgap tuning and low-cost manufacturing based on solution processes. In addition, spectral matching with the silicon bottom cell is possible by precisely tuning the bandgap through mixed cation and mixed halide compositions. The problem to be solved
[0005] For perovskites used as the top absorption layer in perovskite / silicon tandem solar cells, mixed cation and mixed halide compositions are widely applied due to the advantage of easy bandgap tuning. However, the application of such mixed compositions can lead to phase inhomogeneity, where the component distribution within the material is formed unevenly. Phase inhomogeneity forms charge transport barriers due to compositional differences and increases charge recombination losses, thereby degrading photoelectric conversion efficiency and long-term stability.
[0006] Therefore, a manufacturing technology capable of suppressing phase non-uniformity and forming high-quality perovskite thin films with a uniform composition is required.
[0007] The problems to be solved by the embodiments of the present disclosure are not limited to those described above, and problems not mentioned will be clearly understood by those skilled in the art from the present specification and the accompanying drawings. means of solving the problem
[0008] A method for manufacturing a perovskite thin film according to one embodiment comprises the steps of preparing a precursor solution comprising two or more different A-site cations, two or more different halide anions, and a B-site metal cation; applying the precursor solution to a substrate to form a precursor coating layer; and heat-treating the precursor coating layer to manufacture a perovskite thin film, wherein the sum of the moles of two or more different A-site cations in the precursor solution may be greater than the moles of the B-site metal cation.
[0009] A perovskite thin film according to another embodiment can be manufactured according to one embodiment.
[0010] A photoelectric conversion device according to another embodiment may include a perovskite thin film of another embodiment. Effects of the invention
[0011] According to various embodiments of the present disclosure, by designing the composition of the precursor solution non-stoichiometrically, phase non-uniformity in a perovskite thin film having a mixed cation and mixed halide composition can be suppressed and compositional uniformity can be improved.
[0012] In addition, by forming a thin film of uniform composition, stable crystal growth can be maintained even during high-temperature heat treatment processes, and the photoelectric properties and process reproducibility of the device can be improved.
[0013] The effects of the embodiments are not limited to the effects described above, and unmentioned effects will be clearly understood by those skilled in the art from this specification and the accompanying drawings. Brief explanation of the drawing
[0014] FIG. 1 is a cross-sectional view schematically illustrating a photoelectric conversion element according to one embodiment. FIG. 2a is a cross-sectional view schematically illustrating an example of a photoelectric conversion device having an inverted structure according to another embodiment. FIG. 2b is a cross-sectional view schematically illustrating an example of a photoelectric conversion device having a positive structure according to another embodiment. FIG. 3 is a cross-sectional view schematically illustrating a multi-junction photoelectric conversion device according to another embodiment. FIG. 4 is a cross-sectional view schematically illustrating a multi-junction photoelectric conversion device according to another embodiment. FIG. 5 is a cross-sectional view schematically illustrating an example of a multi-junction photoelectric conversion device of FIG. 3. FIG. 6a is a cross-sectional view schematically illustrating a second subcell according to one embodiment of the multi-junction photoelectric conversion device of FIG. 5. FIG. 6b is a cross-sectional view schematically illustrating a second subcell according to another embodiment of the multi-junction photoelectric conversion device of FIG. 5. FIG. 7 is an exploded perspective view schematically illustrating a photoelectric conversion module according to another embodiment. FIG. 8 is a schematic diagram showing the energy level alignment of the perovskite thin films prepared in Comparative Example 1b and Example 1b. Figure 9 is a graph showing the X-ray photoelectron spectroscopy (XPS) analysis results of the perovskite thin films prepared in Comparative Example 1b and Example 1b. Figure 10 is a graph showing the X-ray diffraction (XRD) analysis results of the perovskite thin films prepared in Comparative Example 1b and Example 1b. FIG. 11 is a graph comparing the photoelectric conversion efficiency (PCE) of photoelectric conversion devices prepared in Example 2, Comparative Example 2, and Comparative Example 3. FIG. 12 is a graph comparing the photoelectric conversion efficiency (PCE) of photoelectric conversion devices prepared in Example 2 and Comparative Example 4. FIG. 13 is a graph comparing the open-circuit voltage (Voc) of photoelectric conversion devices manufactured in Example 2, Comparative Example 2, and Comparative Example 3. FIG. 14 is a graph comparing the hysteresis index (HI) of photoelectric conversion devices prepared in Example 2, Comparative Example 2, and Comparative Example 3. Specific details for implementing the invention
[0015] The terms used in the embodiments have been selected to be as widely used as possible, taking into account their functions in the present invention; however, these terms may vary depending on the intent of those skilled in the art, case law, the emergence of new technologies, etc. Additionally, in specific cases, terms have been arbitrarily selected by the applicant, and in such cases, their meanings will be described in detail in the relevant description of the invention. Therefore, terms used to describe the present invention must be defined not merely by their names, but based on their meanings and the content throughout the specification.
[0016] When a part of a specification is described as "including" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.
[0017] Throughout the specification, when expressions such as "at least one" appear before arranged components, they modify the entire set of components rather than each individual component. For example, the expression "at least one of a, b, and c" should be interpreted as including a, b, and c, or a and b, a and c, b and c, or a, b, and c.
[0018] Additionally, throughout the specification, "region" refers to a part having at least one function, which may include multiple components and is not limited to a layered structure but may include a single-layer or multi-layered structure.
[0019] Throughout the specification, terms such as "first-", "second-", etc., are used not in a limiting sense but for the purpose of distinguishing one component from another.
[0020] Terms such as "above," "upper," or "below" and "lower" used throughout the specification are used merely to facilitate the description of the relationships between the components illustrated in the drawings and do not limit the direction in which the components are positioned. Furthermore, when a component is described as being positioned above or on top of another component, it includes not only cases where it is directly above the other component, but also cases where other components are interposed between them. Similarly, when a component is described as being positioned below or on the lower side of another component, it includes not only cases where it is directly below the other component, but also cases where other components are interposed between them.
[0021] Furthermore, the description order of components throughout the specification does not imply an arrangement or stacking order of the components. That is, when multiple components are described as being included, the listed components may be arranged or stacked in various orders, rather than in the order in which they are listed.
[0022] Throughout the specification, the term “region” refers to any structure containing various forms of components that perform the same or similar functions. For example, a region may refer to a structure containing multiple layers of components. Additionally, a region may refer to a structure containing a single layer of components.
[0023] Throughout the specification, the term "layer" refers to any structure in the form of a sheet (e.g., substantially extending in two vertical directions but limited to extension in a third vertical direction). The layer may have a thickness that varies over the range of the layer. Typically, the layer has an approximately constant thickness.
[0024] Throughout the specification, the term "thickness" of a layer refers to the average thickness of the layer. The thickness of the layer can be easily measured, for example, by using a microscopy method such as electron microscopy on a cross-section of the film, or, for example, by a surface shape measurement method using a stylus profilometer.
[0025] Below, embodiments are described in detail with reference to the attached drawings so that a person skilled in the art can easily implement the embodiments. In the drawings, the size or thickness of the components may be exaggerated or reduced for convenience of explanation. The thickness of each layer shown in the drawings does not represent the actual thickness, nor does the relative difference in thickness between the layers represent the difference in actual thickness.
[0026] The embodiments may be implemented in various different forms and are not limited to the embodiments described herein.
[0027] FIG. 1 is a cross-sectional view schematically illustrating a photoelectric conversion element according to one embodiment.
[0028] According to one embodiment, the photoelectric conversion element (100) may include a first electrode (101), a second electrode (102), and a photoelectric conversion region (110). The photoelectric conversion region (110) may be located between the first electrode (101) and the second electrode (102). The photoelectric conversion element (100) may be a single-junction photoelectric conversion element (100).
[0029] The photoelectric conversion device (100) refers to a device having the function of absorbing light energy and converting light energy into electrical energy. The photoelectric conversion device (100) may sequentially include a first electrode (101), a photoelectric conversion region (110), and a second electrode (102) based on the direction of light incidence. Although not limited thereto, the photoelectric conversion device (100) may include a photoelectric conversion region (110) comprising a perovskite material. A detailed explanation thereof will be provided later in the description of the photoelectric conversion region (110).
[0030] Each layer included in the photoelectric conversion device (100) may be formed by one or more methods selected from the group consisting of spin coating, blade coating, slot coating, dip coating, reverse roll coating, forward roll coating, gravure coating, microgravure coating, curtain coating, atomic layer deposition (ALD), and chemical vapor deposition (CVD). However, the method of forming each layer of the photoelectric conversion device (100) is not limited to these methods.
[0031] Throughout the specification, the term "electrode" refers to a conductive material or object that allows current to flow in and out of an object, substance, or area.
[0032] Referring to FIG. 1, the first electrode (101) may be a front electrode. A front electrode refers to an electrode provided on one side or surface of a photoelectric conversion element (100) where light is incident. For example, the first electrode (101) refers to an electrode placed on one side or surface of an element intended to be exposed to light.
[0033] When the first electrode (101) is a front electrode, light incident on the first electrode (101) can pass through the first electrode (101) and be transmitted to the photoelectric conversion region (110). The first electrode (101) includes a light-transmitting material.
[0034] Translucent materials refer to materials or objects that possess the property of allowing light to pass through. Highly translucent materials can generally exhibit transparent or semi-transparent properties. "Transparent" refers to the degree to which light can pass through with almost no obstruction, allowing objects behind them to be clearly visible. "Semi-transparent" refers to having a transmittance that transmits light to an extent intermediate between transparent and opaque. Light transmittance can be measured using general methods, for example, by comparing the intensity of incident light with the intensity of transmitted light.
[0035] According to an embodiment, the first electrode (101) may include a metal layer and a transparent conductive layer. For example, the first electrode (101) may include a patterned metal layer formed on the transparent conductive layer. The transparent conductive layer may transmit light while simultaneously being conductive. By including a patterned metal layer on the transparent conductive layer, light can be transmitted to the lower part of the first electrode (101), and the first electrode (101) can efficiently collect current.
[0036] The patterned metal layer may include fingers and a bus bar. The fingers collect current in microscopic units, and the bus bar collects current from the fingers and transmits it to an external circuit. The bus bar may be formed on the surface of the first electrode (101) and on the surface of the second electrode (102) to be described later. However, the embodiments are not limited by the location and structure of the bus bar described above.
[0037] The first electrode (101) may include additional layers in addition to the metal layer and the transparent conductive layer.
[0038] The metal layer included in the first electrode (101) may include at least one of gold (Au), silver (Ag), and copper (Cu), and may include a composite metal or alloy comprising two or more of the metals. However, the embodiments are not limited by the material of the metal layer described above.
[0039] The thickness of the first electrode (101) can be set considering the resistance and optical loss of the electrode. For example, the thickness of the first electrode (101) can be 50 nm to 2000 nm, 60 nm to 1800 nm, 70 nm to 1600 nm, 80 nm to 1400 nm, 90 nm to 1200 nm, 100 nm to 1000 nm, 120 nm to 800 nm, or 150 nm to 600 nm.
[0040] The transparent conductive layer included in the first electrode (101) may include a transparent conductive oxide (TCO). A transparent conductive oxide refers to a material in the form of an oxide that transmits light and has an electrical conductivity of a certain level or higher.
[0041] Transparent conductive oxides can be in a metal-doped or undoped form. Transparent conductive oxides may include AZO (Aluminum-doped Zinc Oxide), FTO (Fluorine-doped Tin Oxide), GZO (Gallium Zinc Oxide), ZTO (Zinc Tin Oxide), or ZITO (Zinc Indium Tin Oxide).
[0042] In addition, the transparent conductive layer may include carbon nanotubes, silver nanowires, or graphene, replacing or together with the transparent conductive oxide.
[0043] However, the material included in the transparent conductive layer is not limited to the material described above.
[0044] The thickness of the transparent conductive layer can be selected depending on the material used. For example, when a transparent conductive oxide is used as the material of the transparent conductive layer, it may have a thickness in the range of 40 to 200 nm, 50 to 180 nm, 60 to 160 nm, 70 to 140 nm, or 80 to 120 nm.
[0045] According to an embodiment, the first electrode (101) may include a substrate. The substrate may serve as a base that supports the first electrode (101). For example, a transparent conductive layer may be deposited on the substrate, and the substrate may serve as a protective layer for the first electrode (101). For example, the substrate included in the first electrode (101) may include glass or plastic, etc.
[0046] For example, the thickness of the first electrode (101) may be 50 nm to 2000 nm, 60 nm to 1800 nm, 70 nm to 1600 nm, 80 nm to 1400 nm, 90 nm to 1200 nm, 100 nm to 1000 nm, 120 nm to 800 nm, or 150 nm to 600 nm.
[0047] According to the embodiment, the photoelectric conversion region (110) is a region capable of generating an electrical response in response to light. Specifically, the photoelectric conversion region (110) can absorb the energy of a photon to generate an electron-hole pair or an exciton.
[0048] According to the embodiment, the thickness of the photoelectric conversion region (110) may be 300 nm to 3000 nm, 400 nm to 2000 nm, or 500 nm to 1500 nm.
[0049] The photoelectric conversion region (110) may have a multilayer structure. The photoelectric conversion region (110) may include a perovskite material. A detailed description of the photoelectric conversion region (110) will be provided later through FIGS. 2a and 2b.
[0050] Referring to FIG. 1, the second electrode (102) may be a rear electrode. A rear electrode refers to an electrode provided on the opposite side or opposite surface of the photoelectric conversion element (100) where light is incident. For example, the second electrode (102) refers to an electrode provided on the opposite side or opposite surface of the photoelectric conversion element (100) where the first electrode (101) is located. Light transmitted through the photoelectric conversion region (110) may be reflected by the second electrode (102), and the optical path may be increased by reflection. Additionally, the second electrode (102) may collect current.
[0051] The second electrode (102) may include a transparent material or a non-transparent material.
[0052] The second electrode (102) may include a patterned metal layer formed on a transparent conductive layer. Alternatively, the second electrode (102) may include a metal layer without a pattern formed thereon. The metal layer may be a single layer. Alternatively, the metal layer may be a multilayer. However, the embodiments are not limited by the structure of the second electrode (102) described above.
[0053] For example, the second electrode (102) may comprise a metal and / or a transparent conductive oxide. The second electrode (102) may comprise one or more metal atoms selected from the group consisting of gold (Au), silver (Ag), copper (Cu), aluminum (Al), nickel (Ni), palladium (Pd), and platinum (Pt).
[0054] The thickness of the second electrode (102) can be set considering the resistance and optical loss of the electrode. For example, the thickness of the second electrode (102) can be 10 nm to 500 nm, 50 nm to 200 nm, 80 nm to 150 nm, or 90 nm to 120 nm.
[0055] FIG. 2a is a cross-sectional view schematically illustrating an example of a photoelectric conversion device having an inverted structure according to another embodiment.
[0056] The photoelectric conversion device (100) is classified into a positive structure (nip type) and an inverted structure (pin type) depending on the stacking order of the electron transport layer (ETL) and the hole transport layer (HTL).
[0057] Referring to FIG. 2a, the photoelectric conversion element (100) may have an inverted structure. The photoelectric conversion element (100) may include a first electrode (101), a second electrode (102), and a photoelectric conversion region (110) located between the first electrode (101) and the second electrode (102). The photoelectric conversion region (110) may include an electron transport region (111), a hole transport region (112), and a light absorption region (113) located between the electron transport region (111) and the hole transport region (112).
[0058] A photoelectric conversion device (100) having an inverse structure may include a structure in which a second electrode (102), a hole transport region (112), a light absorption region (113), an electron transport region (111), and a first electrode (101) are sequentially stacked.
[0059] In the photoelectric conversion device (100), the light absorption region (113) can absorb incident light to generate electron-hole pairs. The electron-hole pairs can be separated and transferred to the electron transport region (111) and the hole transport region (112), respectively. The light absorption region (113) may include one or more layers.
[0060] The light absorption region (113) may include a perovskite material. The light absorption region (113) may be a single-layer structure or a multilayer structure containing a perovskite material. If the light absorption region (113) is a multilayer structure, each layer may contain a different perovskite material. Additionally, within a layer made of one type of perovskite material, a perovskite material of a different composition having a structure such as a columnar shape, plate shape, needle shape, wire shape, or rod shape may be included.
[0061] The photoelectric conversion region (110) may include a perovskite material. The perovskite material can absorb light to generate electron-hole pairs.
[0062] According to the examples, the perovskite material may include a compound represented by Chemical Formula 1.
[0063] [Chemical Formula 1]
[0064] ABX3
[0065] In Chemical Formula 1, A contains one or more monovalent cations, B contains one or more divalent cations, and X contains one or more halogen anions.
[0066] In the above chemical formula 1, A may include one or more selected from the group consisting of organic cations, inorganic cations, and combinations thereof.
[0067] For example, the organic cation is methylammonium (CH3NH3 + , MA + ), formamidinium (HC(NH2)2 + , FA + ), and ethylammonium (CH3CH2NH3 + , EA + It may include one or more selected from the group consisting of ). In addition, for example, the inorganic cation is Cs + , Rb + , Cu + , Pd + , Pt + , Ag + , Au + , Rh + , and Ru + It may include one or more selected from a group consisting of
[0068] Among the above chemical formula 1, A can be represented by chemical formula 1-1.
[0069] [Chemical Formula 1-1]
[0070] A 1 x A 2 1-x
[0071] In Chemical Formula 1-1, A 1 It may contain one or more organic cations, and A2 It may contain one or more inorganic cations.
[0072] In Chemical Formula 1-1, 0 ≤ x ≤ 1 (x may be a real number between 0 and 1).
[0073] In Chemical Formula 1-1, when x is 0, organic cations are not included, and in Chemical Formula 1-1, when x is 1, inorganic cations are not included.
[0074] For example, A 1 methylammonium (CH3NH3 + ), formamidinium (HC(NH2)2 + ), and ethylammonium (CH3CH2NH3 + It may include one or more selected from a group consisting of ). Also, for example, A 2 is Cs + , Rb + , Cu + , Pd + , Pt + , Ag + , Au + , Rh + , and Ru + It may include one or more selected from a group consisting of
[0075] For example, A in Chemical Formula 1-1 1 HC(NH2)2 + and, A 2 is Cs + It may be. In this case, Chemical Formula 1-1 is [HC(NH)2)2] + x Cs + 1-x It can be displayed as.
[0076] For example, A in Chemical Formula 1-1 1 methylammonium (CH3NH3 + ) and formamidinium (HC(NH2)2 + It may include ). In this case, A in Chemical Formula 1-1 1 [CH3NH3] +x1 [HC(NH2)2] + x2 It can be expressed as. The sum of x1 and x2 can be x.
[0077] For example, A in Chemical Formula 1-1 2 is Cs + and Rb + It may include. In this case, A in Chemical Formula 1-1 2 is Cs + x3 Rb + x4 It can be expressed as. The sum of x3 and x4 can be 1-x.
[0078] For example, in the above chemical formula 1, B is Pb 2+ and Sn 2+ It may include one or more divalent inorganic cations selected from the group consisting of
[0079] For example, in the above chemical formula 1, X is -F - , -Cl - , -Br - and -I - It may include one or more halogen anions selected from the group consisting of. For example, X may not only include one type of halogen anion, but may also include two or more types of halogen anions.
[0080] Among the above chemical formula 1, X3 can be expressed as chemical formula 1-2.
[0081] [Chemical Formula 1-2]
[0082] X 1 y X 2 3-y
[0083] In chemical formula 1-2, X 1 and X 2 are independent of each other, -F - , -Cl - , -Br - and -I -It may include one or more halogen anions selected from the group consisting of
[0084] In chemical formula 1-2, 0 ≤ y ≤ 3 (y can be a real number between 0 and 3).
[0085] For example, X in Chemical Formula 1-2 1 -Br - and X 2 -I - It may be. In this case, Chemical Formula 1-2 is -Br - y I - 3-y It can be displayed as.
[0086] When a perovskite material is included in the light absorption region (113), the thickness of the layer including the perovskite material may be 100 nm to 1000 nm, 200 nm to 800 nm, or 300 nm to 600 nm.
[0087] The electron transport region (111) can be electrically in contact with the light absorption region (113). Electrical contact means that the charge transfer path is maintained even if physically different components are involved. In the photoelectric conversion device (100) having an inverted structure as in FIG. 2a, the electron transport region (111) can be located between the first electrode (101) and the light absorption region (113).
[0088] The electron transport region (111) can selectively transport electrons generated in the light absorption region (113) to the electrode. In a structure like that of FIG. 2a, the electron transport region (111) can transport electrons generated in the light absorption region (113) to the first electrode (101).
[0089] The electron transport region (111) may include one or more layers. The electron transport region (111) may include an electron transport layer (not shown). The electron transport layer may selectively transport electrons generated in the light absorption region (113) and deliver them to the electrode.
[0090] Additionally, although not illustrated, the electron transport region (111) may further include a hole blocking layer (HBL). The hole blocking layer can suppress the movement of holes generated in the light absorption region (113) so as to induce electrons to move selectively toward the electrode.
[0091] Additionally, although not illustrated, the electron transport region (111) may further include an electron injection layer (EIL). The electron injection layer may serve as an auxiliary layer included to improve electron injection efficiency.
[0092] However, the electronic transport region (111) may include other layers in addition to the layer described above.
[0093] The electron transport layer may include an n-type material. The n-type material may have electron transport properties. For example, although not specifically limited, the n-type material may include an inorganic n-type material, an organic n-type material, or both an inorganic n-type material and an organic n-type material.
[0094] The inorganic n-type material may be one or more selected from the group consisting of: oxides containing one or more metal atoms selected from the group consisting of titanium (Ti), tin (Sn), zinc (Zn), niobium (Nb), tantalum (Ta), indium (In), gallium (Ga), and tungsten (W); sulfides containing one or more metal atoms selected from the group consisting of cadmium (Cd), tin (Sn), and zinc (Zn); selenides containing one or more metal atoms selected from the group consisting of cadmium (Cd), zinc (Zn), indium (In), and gallium (Ga); and tellurides containing one or more metal atoms selected from the group consisting of cadmium (Cd), zinc (Zn), cadmium (Cd), and tin (Sn). However, the embodiments are not limited to the inorganic n-type material described above. For example, the inorganic n-type material may include one or more selected from the group consisting of TiO2, ZnO, and SnO2.
[0095] The organic n-type material may be one or more selected from the group consisting of fullerene (C60), fullerene derivatives, perylene derivatives, and NDI (naphthalene diimide)-based polymer compounds. However, the examples are not limited to the organic n-type materials described above. For example, a fullerene derivative is PCBM ([6,6]-Phenyl-C 61 It may include -butyric acid methyl ester). For example, an NDI-based polymer compound may include P(NDI2OD-T2)(Poly{[N,N'-bis(2-octyldodecyl)-1,4,5,8-naphthalene diimide]-alt-5,5'-(2,2'-bithiophene)}).
[0096] In the electron transport region (111), the thickness of the electron transport layer may be 10 nm to 50 nm, 15 nm to 45 nm, 20 nm to 40 nm, or 25 nm to 35 nm.
[0097] The hole transport region (112) can be electrically in contact with the light absorption region (113). In the photoelectric conversion device (100) having an inverted structure as in FIG. 2a, the hole transport region (112) can be located between the second electrode (102) and the light absorption region (113).
[0098] The hole transport region (112) can selectively transport holes generated in the light absorption region (113) and deliver them to the electrode. In a structure like that of FIG. 2a, the hole transport region (112) can deliver holes generated in the light absorption region (113) to the second electrode (102).
[0099] The hole transport region (112) may include one or more layers. The hole transport region (112) may include a hole transport layer (not shown). The hole transport layer can selectively transport holes generated in the light absorption region (113) and deliver them to the electrode.
[0100] Additionally, although not illustrated, the hole transport region (112) may further include an electron blocking layer (EBL). The electron blocking layer can inhibit the movement of electrons generated in the light absorption region (113), thereby inducing holes to move selectively toward the electrode.
[0101] Additionally, although not illustrated, the hole transport region (112) may further include a hole injection layer (HIL). The hole injection layer may serve as an auxiliary layer included to improve hole injection efficiency.
[0102] However, the hole transport area (112) may include other layers in addition to the layer described above.
[0103] The hole transport layer may include one or more p-type materials. The p-type material may have hole transport properties. Although not particularly limited, the p-type material may include an inorganic p-type material, an organic p-type material, or both an inorganic p-type material and an organic p-type material.
[0104] The inorganic p-type material may be one or more selected from the group consisting of: an oxide comprising one or more metal atoms selected from the group consisting of nickel (Ni), vanadium (V), copper (Cu), indium (In), and molybdenum (Mo); a halide comprising one or more metal atoms selected from the group consisting of nickel (Ni), vanadium (V), copper (Cu), indium (In), and molybdenum (Mo); a chalcogenide comprising one or more metal atoms selected from the group consisting of nickel (Ni), vanadium (V), copper (Cu), indium (In), and molybdenum (Mo); and a thiocyanide comprising one or more metal atoms selected from the group consisting of nickel (Ni), vanadium (V), copper (Cu), indium (In), and molybdenum (Mo). However, the embodiments are not limited by the inorganic p-type material described above. For example, the inorganic p-type material is NiO x It may include V2O5.
[0105] The organic p-type material may be one or more selected from the group consisting of triphenylamine-based compounds, carbazole-based compounds, and thiophene-based polymer compounds. However, the examples are not limited to the organic p-type materials described above. For example, the triphenylamine-based compound may include spiro-MeOTAD (2,2',7,7'-Tetrakis(N,N-di-p-methoxyphenylamine)-9,9'-spirobifluorene). For example, carbazole compounds may include PVK (Poly(N-vinylcarbazole)), and / or 2PACz ([2-(9H-Carbazol-9-yl)ethyl]phosphonic Acid). For example, thiophene polymer compounds may include P3HT (poly(3-hexylthiophene)). For example, thiophene polymer compounds may include PEDOT (Poly(3,4-ethylenedioxythiophene)). For example, organic p-type materials may include PEDOT:PSS (Poly(3,4-ethylenedioxythiophene):Poly(styrenesulfonate)).
[0106] In the hole transport region (112), the thickness of the hole transport layer may be 10 nm to 500 nm, 15 nm to 250 nm, 20 nm to 100 nm, 25 nm to 80 nm, or 30 nm to 50 nm.
[0107] Although not illustrated, the photoelectric conversion element (100) may further include a passivation region in addition to the first electrode (101), second electrode (102), electron transport region (111), hole transport region (112), and light absorption region (113) described above. The passivation region may be formed as a single layer or a multilayer.
[0108] The passivation region can chemically or electrically deactivate defects that may occur on the surface or interface of the light absorption region (113), thereby suppressing the recombination of electrons and holes.
[0109] For example, the passivation region may be included between the light absorption region (113) and the electron transport region (111), or between the light absorption region (113) and the hole transport region (112). However, the embodiments are not limited by the location of the passivation region described above.
[0110] The passivation region may include one or more selected from the group consisting of lithium fluoride (LiF), cesium fluoride (CsF), sodium fluoride (NaF), potassium fluoride (KF), magnesium fluoride (MgF2), aluminum fluoride (AlF3), aluminum oxide (Al2O3), and calcium fluoride (CaF2). However, the embodiments are not limited by the material of the passivation region described above.
[0111] FIG. 2b is a cross-sectional view schematically illustrating an example of a photoelectric conversion device having a positive structure according to another embodiment.
[0112] Referring to FIG. 2b, the photoelectric conversion element (100) may have a regular structure. The photoelectric conversion element (100) may include a first electrode (101), a second electrode (102), and a photoelectric conversion region (110) located between the first electrode (101) and the second electrode (102). The photoelectric conversion region (110) may include an electron transport region (111), a hole transport region (112), and a light absorption region (113) located between the electron transport region (111) and the hole transport region (112).
[0113] A photoelectric conversion device (100) having a positive structure may include a structure stacked in the order of a second electrode (102), an electron transport region (111), a light absorption region (113), a hole transport region (112), and a first electrode (101).
[0114] FIG. 3 is a cross-sectional view schematically illustrating a multi-junction photoelectric conversion device according to another embodiment.
[0115] The multi-junction photoelectric conversion device (200) includes two or more subcells, and the subcells are electrically connected to each other. Specifically, the subcells may have different band gaps and may be stacked in series. As a result, the utilization rate of the optical spectrum may be improved.
[0116] Referring to FIG. 3, the multi-junction photoelectric conversion device (200) may have a tandem structure including two subcells. The multi-junction photoelectric conversion device (200) may include a first electrode (201); a second electrode (202); a first subcell (210); a second subcell (220); and a recombination region (230). A description of the recombination region (230) will be given later with reference to FIG. 5.
[0117] Specifically, the multi-junction photoelectric conversion element (200) may include a pair of electrodes (201, 202) and may include a structure in which a first subcell (210) and a second subcell (220) are electrically connected by a recombination region (230).
[0118] The multijunction photoelectric conversion device (200) may have various structures depending on the combination of subcells. For example, in the case of a multijunction photoelectric conversion device (200) including two subcells, it may have a perovskite-silicon tandem structure, a heterogeneous perovskite tandem structure, a perovskite-CdTe tandem structure, a perovskite-CuZnSnSSe tandem structure, a perovskite-CuZnSnS tandem structure, and a perovskite-CIGS tandem structure. However, the embodiments are not limited by the structure of the multijunction photoelectric conversion device (200) described above.
[0119] According to the embodiment, the first subcell (210) may be a perovskite subcell, and the second subcell (220) may be a silicon subcell. In this case, the first subcell (210) may absorb light of a relatively short wavelength, and the second subcell (220) may absorb light of a relatively long wavelength. As a result, the utilization rate of the optical spectrum may be improved compared to a single-junction photoelectric conversion device. For example, the first subcell (210) mainly absorbs light in the 400 nm to 750 nm range, and the second subcell (220) mainly absorbs light in the 750 to 1100 nm range.
[0120] FIG. 4 is a cross-sectional view schematically illustrating a multi-junction photoelectric conversion device according to another embodiment.
[0121] Referring to FIG. 4, the multi-junction photoelectric conversion element (200) may include more than two subcells.
[0122] Specifically, the multi-junction photoelectric conversion element (200) includes a pair of electrodes (201, 202), a reconnection region (230) between a first subcell (210) and a second subcell (220), and may further include n additional subcells and n additional reconnection regions (250).
[0123] For example, a multi-junction photoelectric conversion device (200) may include a triple subcell structure. Specifically, the triple subcell structure may include a first electrode (201); a second electrode (202); a first subcell (210); a second subcell (220); a recombination region (230); and one additional subcell and one additional recombination region (250).
[0124] For example, the triple subcell structure may be a perovskite-perovskite-silicon structure or a perovskite-silicon-perovskite structure. However, the embodiments are not limited to the triple subcell structure described above.
[0125] FIG. 5 is a cross-sectional view schematically illustrating an example of a multi-junction photoelectric conversion device of FIG. 3.
[0126] Referring to FIG. 5, a multi-junction photoelectric conversion device (200) includes a first electrode (201) and a second electrode (202). A first subcell (210) and a second subcell (220) are disposed between the pair of electrodes (201, 202). The first subcell (210) and the second subcell (220) include a structure in which they are electrically connected by a recombination region (230).
[0127] According to the embodiment, the first subcell (210) may be a perovskite subcell, and the second subcell (220) may be a silicon subcell. The first light-absorbing region (213) of the first subcell (210) may include a perovskite material, and the second subcell (220) may include a silicon material. The structure of the second subcell (220) will be described later with reference to FIGS. 6a and 6b.
[0128] The first subcell (210) may include a first electron transport region (211), a first hole transport region (212), and a first light absorption region (213). The first light absorption region (213) may be positioned between the first electron transport region (211) and the second hole transport region (212).
[0129] The description of the first electron transport region (211) is based on the description of the electron transport region (111) described above through FIG. 2a. The description of the first hole transport region (212) is based on the description of the hole transport region (112) described above through FIG. 2a. The description of the first light absorption region (213) is based on the description of the light absorption region (113) described above through FIG. 2a.
[0130] The second subcell (220) can serve as the basis for a multi-junction photoelectric conversion device (200). Specifically, the first subcell (210) may be stacked on the second subcell (220). A recombination region (230) is included between the first subcell (210) and the second subcell (220).
[0131] The recombination region (230) can electrically and physically connect the first subcell (210) and the second subcell (220). In the recombination region (230), electrons or holes from the first subcell (210) and holes or electrons from the second subcell (220) can be recombinated.
[0132] The recombination region (230) may be formed as a single layer or multiple layers. The recombination region (230) may include an interconnection layer (ICL).
[0133] The recombination region (230) can transmit light and simultaneously have hole affinity and electron affinity. Any material that can be used conventionally as a material included in the recombination region (230) may be used without limitation, but may include one or more selected from the group consisting of transparent conductive oxides, carbon-based conductive materials, and silicon-based conductive materials.
[0134] For example, transparent conductive oxides may include AZO (Aluminum-doped Zinc Oxide), FTO (Fluorine-doped Tin Oxide), GZO (Gallium Zinc Oxide), ZTO (Zinc Tin Oxide), or ZITO (Zinc Indium Tin Oxide). For example, carbon-based conductive materials may include graphene. For example, silicon-based conductive materials may include nc-Si:H (Hydrogenated Nano-crystalline Silicon).
[0135] In the recombination region (230), the thickness of the interconnect layer may be 5 nm to 200 nm, 10 to 150 nm, 20 to 100 nm, or 30 to 50 nm.
[0136] FIG. 6a is a cross-sectional view schematically illustrating a second subcell according to one embodiment of the multi-junction photoelectric conversion device of FIG. 5.
[0137] Specifically, FIG. 6a additionally illustrates a recombination region (230a) and a second electrode (202a) in addition to the second subcell (220a).
[0138] Referring to FIG. 6a, the second subcell (220a) may include an emitter (221a), a base layer (222a), and a rear passivation region (223a). However, it is not limited thereto.
[0139] Although not limited thereto, the second subcell (220a) may include a silicon material. The silicon material may or may not be doped. If doped as p-type, the silicon material may be referred to as a p-type silicon material, and if doped as n-type, the silicon material may be referred to as an n-type silicon material.
[0140] P-type silicon materials may contain one or more atoms selected from the group consisting of boron (B), aluminum (Al), and gallium (Ga). N-type silicon materials may contain one or more atoms selected from the group consisting of nitrogen (N), phosphorus (P), and arsenic (As).
[0141] The silicon material may include one or more selected from the group consisting of crystalline silicon (c-Si) and amorphous silicon (a-Si). The crystalline silicon may include single-crystal silicon, polycrystalline silicon, or a mixed structure of polycrystalline silicon and polycrystalline silicon.
[0142] The base layer (222a) may comprise crystalline silicon (c-Si). The base layer (222a) may absorb light to generate electron-hole pairs. An emitter (221a) may be disposed on the base layer (222a). The emitter (221a) may have a conductivity type opposite to that of the base layer (222a). The emitter (221a) may be disposed between the recombination region (230a) and the base layer (222a).
[0143] The base layer (222a) may be n-type or p-type, and accordingly, the emitter (221a) disposed on the base layer (222a) may be p-type or n-type. If referred to as n-type, an n-type silicon material may be included in the base layer (222a). If referred to as p-type, a p-type silicon material may be included in the base layer (222a).
[0144] As an example, if the second subcell (220a) has a PERC (Passivated Emitter and Rear Contact) structure, the base layer (222a) may be p-type and the emitter (221a) may be n-type. As another example, if the second subcell (220a) has a TOPCon (Tunnel Oxide Passivated Contact) structure, the base layer (222a) may be n-type and the emitter (221a) may be p-type.
[0145] As the emitter (221a) and the base layer (222a) have opposite conductivity types, a PN junction is formed at the interface between the emitter (221a) and the base layer (222a). As the PN junction is formed, electrons and holes generated through light absorption can be separated. The separated electrons and holes can be selectively transported and move toward the electrode to generate current.
[0146] Additionally, the second subcell (220a) may include a rear passivation region (223a). The rear passivation region (223a) may be positioned between the base layer (222a) and the second electrode (202a) to reduce electron-hole recombination. The rear passivation region (223a) may be formed as a single layer or a multilayer. The rear passivation region (223a) may be positioned between the base layer (222a) and the second electrode (202a).
[0147] Meanwhile, the second subcell (220a) may include additional layers as needed in addition to the emitter (221a), base layer (222a), and rear passivation region (223a). For example, the second subcell (220a) may include additional layers to prevent light reflection.
[0148] FIG. 6b is a cross-sectional view schematically illustrating a second subcell according to another embodiment of the multi-junction photoelectric conversion device of FIG. 5.
[0149] Specifically, FIG. 6b additionally illustrates a recombination region (230b) and a second electrode (202b) in addition to the second subcell (220b).
[0150] The second subcell (220b) may include a silicon material. Referring to FIG. 6b, the second subcell (220b) may include a first doping layer (221b), a first non-doping layer (222b), a base layer (223b), a second non-doping layer (224b), and a second doping layer (225b). However, the embodiments are not limited by the material of the second subcell (220b) described above.
[0151] The base layer (223b) may include crystalline silicon. The first doping layer (221b), the first non-doping layer (222b), the second non-doping layer (224b), and the second doping layer (225b) may include amorphous silicon (a-Si). The second subcell (220b) may have a silicon heterojunction (SHJ) structure in which crystalline silicon and amorphous silicon are joined.
[0152] Additionally, the first doping layer (221b) may have a conductivity type opposite to that of the base layer (223b). By having the first doping layer (221b) positioned in the direction of incident light have a conductivity type opposite to that of the base layer (223b), a PN junction including the first non-doping layer (222b) can be formed.
[0153] For example, the base layer (223b) and the second doping layer (225b) may be n-type independently of each other. The first doping layer (221b) may be p-type. Conversely, the base layer (223b) and the second doping layer (225b) may be p-type independently of each other. The first doping layer (221b) may be n-type.
[0154] An intrinsic silicon layer may be formed on the upper and lower portions of the base layer (223b), respectively. That is, a first non-doped layer (222b) may be located on the upper portion of the base layer (223b), and a second non-doped layer (224b) may be located on the lower portion of the base layer (223b).
[0155] Additionally, a first doping layer (221b) may be located on top of the first non-doping layer (222b), and a second doping layer (225b) may be located on the bottom of the second non-doping layer (224b). The first doping layer (221b) and the second doping layer (225b) may have opposite conductivity types.
[0156] FIG. 7 is an exploded perspective view schematically illustrating a photoelectric conversion module according to another embodiment.
[0157] The photoelectric conversion module (300) may include a first substrate (310), a second substrate (320), and a plurality of photoelectric conversion elements (330). Specifically, the photoelectric conversion module (300) may include a first substrate (310), a second substrate (320), and a plurality of photoelectric conversion elements (330) that are disposed between the first substrate (310) and the second substrate (320) and are electrically connected to each other.
[0158] A plurality of photoelectric conversion elements (330) are electrically connected to the above-described photoelectric conversion elements (see 100 in FIG. 1). A plurality of photoelectric conversion elements (330) can be electrically connected to each other through a metal ribbon. Specifically, a plurality of photoelectric conversion elements (330) can be formed by connecting the front electrode of one photoelectric conversion element and the rear electrode of another photoelectric conversion element by a ribbon. The ribbon can connect the busbars of each photoelectric conversion element.
[0159] The first substrate (310) and the second substrate (320) can protect a plurality of photoelectric conversion elements (330) from external shocks, moisture, ultraviolet rays, etc.
[0160] The first substrate (310) may be provided on a surface where light is incident. The first substrate (310) includes a light-transmitting material. The first substrate (310) may include a material to prevent light reflection and increase light transmittance. The first substrate (310) may include a first sheet (310a), a first encapsulant (310b), or a first sheet (310a) and a first encapsulant (310b).
[0161] The second substrate (320) may be provided on the side opposite to the surface where light is incident. The second substrate (320) may include a light-transmitting material or a light-transmitting material. The second substrate (320) may also include a reflective material, etc. The second substrate (320) may include a second sheet (320a), a second encapsulating material (320b), or a second sheet (320a) and a second encapsulating material (320b).
[0162] The first sheet (310a) and the second sheet (320a) can serve as a base supporting the photoelectric conversion module (300). The first sheet (310a) and the second sheet (320a) can protect the exterior of the photoelectric conversion module (300).
[0163] The first sheet (310a) can transmit light. For example, the first sheet (310a) may include glass and / or plastic. The second sheet (320a) may or may not transmit light. For example, the second sheet (320a) may include PVF (Polyvinyl Fluoride) / PET (Polyethylene Terephthalate) / PVF.
[0164] The first encapsulant (310b) and the second encapsulant (320b) can seal a plurality of photoelectric conversion elements (330). The first encapsulant (310b) and the second encapsulant (320b) can protect a plurality of photoelectric conversion elements (330). The first encapsulant (310b) and the second encapsulant (320b) can be bonded by a lamination process. The first encapsulant (310b) and the second encapsulant (320b) can each be cured.
[0165] The first encapsulant (310b) and the second encapsulant (320b) may include a thermosetting resin. For example, they may include one or more selected from the group consisting of EVA (Ethylene-Vinyl Acetate), POE (Polyolefin Elastomer), and TPU (Thermoplastic Polyurethane).
[0166] A method for manufacturing a perovskite thin film according to one embodiment may include the steps of preparing a precursor solution, applying the precursor solution to a substrate to form a precursor coating layer, and heat-treating the precursor coating layer to manufacture a perovskite thin film.
[0167] According to one embodiment, the precursor solution may include two or more different A-site cations, two or more different halide anions, and B-site metal cations. The sum of the moles of two or more different A-site cations may be greater than the moles of B-site metal cations.
[0168] In conventional perovskite thin film fabrication, it was common practice to set the molar ratio of A-site cations to B-site metal cations to a stoichiometric 1:1. However, with this composition, A-site cations volatilize or reaction deviations occur during the film deposition process, resulting in non-uniform composition within the thin film and consequently causing problems such as phase separation and the formation of charge transfer barriers. In this embodiment, to solve these problems, the A:B molar ratio of the precursor solution is adjusted to be slightly larger than the stoichiometric ratio, thereby maintaining a uniform composition even after film deposition.
[0169] Here, the A-site cation refers to a monovalent cation present at the cation lattice position of the perovskite structure, for example, formamidinium (HC(NH2)2 + , FA + ), methylammonium (CH3NH3 + , MA + ), ethylammonium (CH3CH2NH3 + , EA + Organic cations such as ) or cesium (Cs + ), Rubidium (Rb + It may contain inorganic cations such as ).
[0170] B-site metal cations refer to divalent metal cations located at the central lattice position of the perovskite structure, for example, lead (Pb 2+ ), Comment(Sn 2+ ) etc. can be used.
[0171] Halide anions are anions present in the anionic lattice of perovskites, and chloride (Cl - ), Bromine (Br - ), iodine(I - It may include ) etc.
[0172] Perovskites have the advantage of being easy to control in terms of band gap and absorption spectrum. Due to these characteristics, perovskites can be used as the top absorption layer in tandem solar cells, and in this case, it may be advantageous to apply mixed cation and mixed halide compositions for spectral matching. However, compositional non-uniformity can easily occur due to differences in the reactivity and volatility characteristics of different ions. Consequently, there was a problem in which non-uniformity in charge transport pathways and defect density increased, leading to a decrease in photoelectric efficiency.
[0173] A method according to one embodiment can suppress phase separation during the crystal growth process, mitigate non-uniformity of charge transport paths, and reduce the formation of defects within the lattice by designing the precursor solution non-stoichiometrically. Consequently, compositional uniformity and crystallinity can be simultaneously improved, and a stable crystal structure can be maintained even during high-temperature heat treatment processes. Through this, perovskite thin films with excellent photoelectric conversion efficiency and long-term stability can be manufactured.
[0174] According to one embodiment, the molar ratio of the sum of the moles of two or more different A-site cations and the moles of B-site metal cations in a precursor solution may be about 1.025:1 to about 1.075:1. When the molar ratio is within the above range, compositional non-uniformity during the film formation process is alleviated, and the compositional uniformity of the perovskite thin film can be improved.
[0175] On the other hand, if the total number of moles of A-site cations is less than about 1.025 times the number of moles of B-site metal cations, compositional non-uniformity may occur and photoelectric efficiency may decrease. In addition, if the total number of moles of A-site cations exceeds about 1.075 times, an excess amount of A-site precursor remains and exhibits insulating properties, which may hinder charge transfer.
[0176] For example, the total moles of A-site cations and the molar ratio of B-site metal cations in the precursor solution may be about 1.03:1 to about 1.07:1, about 1.035:1 to about 1.065:1, about 1.04:1 to about 1.06:1, or about 1.045:1 to about 1.055:1.
[0177] According to one embodiment, two or more different A-site cations of the precursor solution may include a first A-site cation and a second A-site cation. The first A-site cation may be an organic cation, and the second A-site cation may be an inorganic cation.
[0178] The first A-site cation can provide flexibility within the lattice of the perovskite crystal structure and play a role in relaxing lattice vibrations. For example, the first A-site cation is methylammonium (CH3NH3 + ), formamidinium (HC(NH2)2 + ), and ethylammonium (CH3CH2NH3 + It may be one or more selected from the group consisting of ). These organic cations have a relatively large ionic radius, which can stabilize charge transfer paths by relaxing inter-crystal gaps and inducing lattice expansion.
[0179] Second A-site cations can play a role in improving the thermal stability and crystallinity of the perovskite structure. For example, the second A-site cation is Cs + , Rb + , Cu + , Pd + , Pt + , Ag + , Au + , Rh + , and Ru + It may be one or more selected from the group consisting of. These inorganic cations have small ionic radii and strong bonding forces, which can improve the thermal and structural stability of the crystal lattice.
[0180] As such, a mixed A-site composition containing different organic and inorganic cations together has the advantage of precisely controlling the lattice constant and band gap while suppressing instability or phase separation problems that occur in each individual composition. Furthermore, charge transfer characteristics and absorption spectra can be controlled depending on the ratio of organic cations, and crystal stability in high-temperature processes can be improved depending on the content of inorganic cations.
[0181] According to one embodiment, the molar ratio of the first A-site cation to the B-site metal cation may be about 0.825:1 to about 0.875:1. The first A-site cation may consist of highly volatile and reactive organic cations, and some of them may be lost by vaporization or decomposition during the film formation and heat treatment processes. Therefore, by adjusting the precursor composition to be slightly excess of the stoichiometry, the loss of A-site cations occurring in the actual thin film after heat treatment can be suppressed.
[0182] If the molar ratio is less than about 0.825:1, the loss of first A-site cations is not sufficiently compensated, which may increase lattice defects (such as vacancies), which may lead to increased charge transfer resistance and degraded photoelectric properties of the thin film. Conversely, if the molar ratio exceeds about 0.875:1, an excess amount of first A-site cations remains, which may increase insulation or induce abnormal crystal growth, thereby degrading the uniformity of the film.
[0183] For example, the molar ratio of the first A-site cation to the B-site metal cation may be about 0.83:1 to about 0.87:1, about 0.835:1 to about 0.865:1, about 0.84:1 to about 0.86:1, or about 0.845:1 to about 0.855:1. Within the above range, a stable lattice structure is maintained even during the heat treatment process, and the compositional uniformity and crystallinity of the final perovskite thin film can be improved.
[0184] In perovskite structures, halide anions form an anionic lattice surrounding B-site metal cations and directly influence crystal growth direction, defect formation energy, and photoelectric properties. When mixed halides are used, compositional non-uniformity is prone to occur during the film deposition process due to differences in the volatility and reactivity of each halide anion, and variations in loss amounts during heat treatment can degrade the anionic lattice stability of the final thin film. Such compositional non-uniformity increases halide vacancies within the lattice, which promotes non-radiative recombination and can degrade the open-circuit voltage and charge transport characteristics of the device.
[0185] According to one embodiment, losses during the film formation and heat treatment processes can be compensated by setting the total number of moles of two or more different halide anions in the precursor solution stage to be slightly in excess of the stoichiometry. The molar ratio of the sum of the number of moles of two or more different halide anions in the precursor solution to the number of moles of B-site metal cations may be about 3.025:1 to about 3.075:1. If the molar ratio is less than about 3.025:1, the halide loss may not be sufficiently compensated, and vacancy defects may increase, and if it exceeds about 3.075:1, an excess amount of halide may remain or abnormal phase separation may occur.
[0186] For example, the above molar ratio may be about 3.03:1 to about 3.07:1, about 3.035:1 to about 3.065:1, about 3.04:1 to about 3.06:1, or about 3.045:1 to about 3.055:1. Within the above range, the anionic lattice is stably maintained even during the heat treatment process, so the crystallinity, compositional uniformity, and photoelectric properties of the thin film can be improved.
[0187] In addition, two or more different types of halide anions may include a first halide anion and a second halide anion, among which the first halide anion is a component that directly contributes to the formation of the main crystal phase. According to one embodiment, the molar ratio of the first halide anion to the B-site metal cation may be about 2.425:1 to about 2.475:1. Since the first halide anion is involved in the formation of the main crystal nucleus during the initial film formation, if the initial supply is insufficient, compositional non-uniformity and vacancy defects may increase, and if introduced in excess, abnormal phase formation or surface non-uniformity may occur.
[0188] For example, the above molar ratio may be about 2.43:1 to about 2.47:1, about 2.435:1 to about 2.465:1, about 2.44:1 to about 2.46:1, or about 2.445:1 to about 2.455:1. Within the above range, the loss of the first halide anion is compensated during the heat treatment process, so that the lattice of the final thin film is stably maintained, and this can contribute to securing crystal growth directionality, reducing defect density, and improving charge transfer characteristics.
[0189] According to one embodiment, the solvent of the precursor solution may include a polar amide-based solvent. For example, the solvent of the precursor solution may include dimethylformamide (DMF), dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), N,N'-dimethylpropylene urea (DMPU), or a combination thereof.
[0190] For example, the solvent of the precursor solution may include dimethylformamide (DMF) and n-methylpyrrolidone (NMP). The volume ratio of dimethylformamide (DMF) and n-methylpyrrolidone (NMP) may be about 8:2 to about 9.5:0.5.
[0191] The above solvent composition can control the crystal growth rate during the film formation process by controlling the viscosity of the precursor solution and the solvent evaporation rate. If the DMF content is excessively high, crystallization proceeds rapidly, which may reduce the uniformity of the thin film; conversely, if the NMP content is excessively high, the evaporation of the solvent is delayed, which may result in non-uniform drying. Therefore, by applying a solvent ratio within the above range, the evaporation and crystallization rates of the solvent can be controlled in a balanced manner, and a perovskite thin film of uniform thickness can be formed. For example, the volume ratio of the solvent may be about 8.5:1.5 to about 9.5:0.5, about 8.7:1.3 to about 9.3:0.7, or about 9:1.
[0192] According to one embodiment, the precursor solution may further include an additive. The additive may include a monovalent alkylammonium halide, for example, methylammonium chloride (MACl), methylammonium iodide (MAI), methylammonium bromide (MABr), ethylammonium chloride (EACl), or a combination thereof.
[0193] These monovalent alkylammonium halides form a transient intermediate phase in the precursor solution, thereby controlling the nucleation process of crystal growth and inducing uniform crystal growth by alleviating the energy barriers at the grain boundaries. Additionally, since the additive evaporates during the heat treatment process and does not remain in the final perovskite crystal, the formation of charge traps caused by impurities in the lattice can be suppressed.
[0194] For example, MACl has high volatility and excellent solubility, allowing it to be rapidly and uniformly dispersed within a precursor solution, and it can be effective in controlling crystal surface energy during the early stages of grain growth. By adding MACl, high-quality perovskite thin films with uniform grain size and low defect density can be formed.
[0195] According to one embodiment, the content of the additive may be about 20 mol% to about 30 mol% based on the molar amount of B-site metal cations. If the additive content is less than 20 mol%, the crystal growth control effect is insufficient and the uniformity of the thin film may be reduced, and if it exceeds 30 mol%, an excess amount of additive remains, which may cause pores to form or the surface of the thin film to become rough during the film formation process.
[0196] For example, the content of the additive may be about 22 mol% to about 28 mol%, about 24 mol% to about 26 mol%, or about 25 mol%. At the above range of additive content, grain growth proceeds uniformly, allowing for the production of a perovskite thin film with excellent photoelectric conversion efficiency and long-term stability.
[0197] According to one embodiment, a precursor coating layer can be formed by a blade coating method. Blade coating is a method in which a predetermined amount of precursor solution is applied, and then a blade is moved at a constant speed to spread the solution thinly, thereby enabling the formation of a coating layer of uniform thickness even on a large-area substrate. Unlike spin coating, blade coating involves less material loss and is easy to scale into a continuous process, making it suitable for manufacturing large-area solar cells.
[0198] The thickness of the precursor coating layer can be controlled according to the blade movement speed, coating temperature, and coating amount; for example, the coating speed can be about 3 mm / s to about 7 mm / s, more specifically about 5 mm / s. The thin film coated under the above conditions has a uniform thickness and composition and can exhibit characteristics with little variation even in large-area samples.
[0199] According to one embodiment, the precursor coating layer can be dried by spraying an inert gas. The inert gas may be nitrogen (N2), argon (Ar), or a mixture thereof, and the spray pressure may be about 0.3 MPa to about 0.7 MPa. If the gas spray pressure is less than 0.3 MPa, the solvent evaporation rate is slow, so the thin film surface may be formed unevenly, and if it exceeds 0.7 MPa, the thin film surface may be damaged by excessive flow.
[0200] For example, the injection pressure of the inert gas can be approximately 0.4 MPa to approximately 0.6 MPa. When the concentration of the A-site cation precursor is increased through the non-stoichiometric composition design of the precursor solution, the evaporation rate of the solvent can be mitigated through interaction with the solvent. Accordingly, even if the injection pressure of the inert gas is set relatively high during the drying process, uniform drying can be achieved without damaging the thin film surface. In other words, the non-stoichiometric composition design improves the physical stability of the precursor solution, allowing drying efficiency and reproducibility to be maintained even under higher pressure conditions.
[0201] According to one embodiment, the heat treatment of the precursor coating layer may be performed in multiple steps. For example, the precursor coating layer may include a first heat treatment step performed at a temperature of 120°C to 200°C and a second heat treatment step performed at a temperature of 50°C to 170°C.
[0202] By performing multiple heat treatment steps, the solvent removal and crystal growth processes can be controlled stepwise, thereby enabling the simultaneous achievement of uniform grain growth and excellent crystallinity.
[0203] The first heat treatment step can be performed to remove the initial solvent from the precursor coating layer. Since the evaporation of the solvent occurs rapidly during the first heat treatment step, the heat transfer method can significantly affect the uniformity of the thin film.
[0204] According to one embodiment, the first heat treatment step can be performed using an inline oven in which heat is transferred by convection. Since convection heat treatment can uniformly heat the entire substrate, the temperature distribution is maintained uniformly even in large-area samples, and thin film damage or non-uniform crystal growth caused by rapid solvent evaporation can be suppressed.
[0205] A second heat treatment step can be performed to stabilize the crystal structure and improve crystallinity. In this second heat treatment step, heat can be transferred using a hot plate that utilizes a conductive heat transfer method. Conductive heat treatment strengthens intergranular bonding and reduces defects in the crystal lattice. In other words, by sequentially applying convection and conductive heat treatments, uniform crystal growth and surface flatness can be secured initially, and subsequently, the completeness of the crystal structure can be improved.
[0206] According to one embodiment, the first heat treatment step may be performed for about 1 minute to about 30 minutes, and the second heat treatment step may be performed for about 5 minutes to about 120 minutes. The heat treatment time can be adjusted according to temperature conditions and thin film thickness, and by controlling within the above range, a balance between the crystal growth rate and the grain size can be maintained.
[0207] Consequently, the multi-step heat treatment process described above can reduce crystallinity variations even in large-area samples and maintain a stable perovskite crystal structure even under high-temperature conditions. Through this, the fabricated perovskite thin films have uniform charge transport paths, and their photoelectric conversion efficiency and long-term stability can be improved.
[0208] According to one embodiment, the thickness of the perovskite thin film may be about 500 nm to about 800 nm. In this thickness range, sufficient light absorption can be secured as a light absorption layer, while the charge transport efficiency can be maintained without the charge transport distance increasing excessively. That is, a balance between light absorption efficiency and charge extraction efficiency is secured, and the photoelectric conversion efficiency of the entire device can be improved.
[0209] If the thickness of the thin film is less than about 500 nm, the absorption rate of incident light is low, which may reduce the photocurrent density, and if the thickness exceeds about 800 nm, the charge transport path becomes longer, which may increase recombination losses. In addition, excessive thickness can cause internal stress accumulation and crack formation during the heat treatment process.
[0210] For example, the thickness of the perovskite thin film may be about 520 nm to about 750 nm, about 550 nm to about 700 nm, or about 600 nm to about 650 nm. At thicknesses within the above ranges, the crystal grains grow uniformly, the surface defect density is low, and a stable crystal structure can be maintained.
[0211] According to one embodiment, the perovskite thin film may have a composition represented by the following chemical formula 1.
[0212] [Chemical Formula 1]
[0213] FA 1-x Cs x Pb(I 1-y Br y )3
[0214] The above FA is formamidinium (HC(NH2)2 + ) and, above x is a real number from 0.1 to 0.3, and above y is a real number from 0.1 to 0.3.
[0215] The above composition is an organic cation (FA). + ) and inorganic cations (Cs + By mixing ), the stability of the crystal structure and thermal stability can be improved simultaneously.
[0216] FA + has high light absorption efficiency but low phase stability, and Cs + This can induce lattice stabilization. Accordingly, the mixed composition of FA and Cs can form a tetragonal structure that is stable compared to the FAPbI3 single phase.
[0217] In addition, halide anions (I - , Br - The ratio (y) of ) can directly affect the bandgap tuning of perovskites. Bromine (Br - As the content increases, the band gap expands, allowing the light absorption spectrum to shift to a short wavelength region, and thus the composition can be suitable as an upper absorption layer for a tandem solar cell combined with a silicon-based bottom cell.
[0218] If x is less than 0.1, Cs + The crystal structure stabilization effect may be insufficient due to an insufficient introduction amount, and if x exceeds 0.3, Cs + Lattice stress non-uniformity may occur due to excess.
[0219] In addition, if y is less than 0.1, the bandgap tuning effect is limited, and if y exceeds 0.3, the light absorption region becomes excessively short-wavelength, which may reduce the photocurrent density.
[0220] For example, x can be 0.15 to 0.25 and y can be 0.15 to 0.25. In this range of compositions, the crystal grains maintain a stable tetragonal structure, and the band gap is adjusted to approximately 1.7 eV, which can exhibit photoelectric properties suitable for tandem cell applications.
[0221] In addition, the x and y values in the composition can be confirmed through X-ray Photoelectron Spectroscopy (XPS) analysis. By quantitatively evaluating the compositional ratio and bonding state of each element, the actual compositional changes of the perovskite thin film according to heat treatment conditions and solution composition can be verified.
[0222] According to one embodiment, the bandgap of the perovskite thin film may be about 1.60 eV to about 1.90 eV. A thin film having a bandgap in the above range can efficiently absorb sunlight across a wide range of wavelengths as a single absorption layer and simultaneously secure a high open-circuit voltage (Voc). Accordingly, it may be suitable not only for a single-cell structure but also as an upper absorption layer of a tandem solar cell combined with a silicon-based bottom cell.
[0223] If the band gap is less than approximately 1.60 eV, bromine (Br - If the bromine content is insufficient, the band gap becomes excessively narrow, and while the current density may be high, the open-circuit voltage loss may increase. Conversely, if the band gap exceeds about 1.90 eV, the bromine content increases excessively, causing the absorption region to shift toward shorter wavelengths and the current density to decrease.
[0224] In addition, the band gap in this embodiment can directly correspond to the I / Br ratio (y) in the composition. For example, when y is in the range of 0.1 to 0.3, the band gap can be adjusted to a range of about 1.60 eV to about 1.90 eV.
[0225] The bandgap can be calculated using the ultraviolet-visible (UV-Vis) absorption spectrum, and the composition ratio (x, y) can be confirmed through X-ray photoelectron spectroscopy (XPS) analysis. Through such analysis, photoelectric properties according to changes in composition can be evaluated, and balanced photocurrent and open-circuit voltage can be realized through composition control.
[0226] A photoelectric conversion device according to another embodiment may include a perovskite thin film prepared according to one embodiment. Since the perovskite thin film prepared according to one embodiment provides a structure with improved compositional uniformity, crystallinity, and energy level alignment, a photoelectric conversion device including the same can improve charge transport characteristics and photoelectric conversion performance.
[0227] For example, the photoelectric conversion device may include a general thin-film photoelectric device structure such as a substrate, a charge transport layer, and a metal electrode, and may be implemented as a single junction or multi-junction structure (e.g., the form shown in FIG. 3) as needed. The perovskite thin film of the present disclosure may be applied to various types of photoelectric conversion devices and may be appropriately modified and used depending on the configuration or manufacturing process of the device.
[0228] Hereinafter, preferred embodiments are presented to aid in understanding the present disclosure. However, these embodiments are intended to explain the present disclosure more specifically, and the scope of the present disclosure is not limited by them. It will be obvious to those skilled in the art that various changes and modifications are possible within the scope and spirit of the present disclosure.
[0229] Example 1a: Preparation of a perovskite thin film
[0230] The precursor solution was prepared as follows. First, FAPbI3 and CsPbBr3 were mixed in a molar ratio of 8:2. To the mixed precursor, 5 mol% of formamidinium iodide (FAI) and 25 mol% of methylammonium chloride (MACl), based on the molar amount of Pb, were added. Dimethylformamide (DMF) and n-methylpyrrolidone (NMP) were used as solvents, with a volume ratio of DMF to NMP of 9:1. The mixed solution was stirred at room temperature for about 12 hours to prepare a homogeneous precursor solution.
[0231] 250 μL of the prepared precursor solution was applied onto a silicon bottom / TCO / HTL / SAM substrate, and a coating layer was formed using a blade coating method. The coating speed was set to approximately 5.0 mm / s. The formed wet film was dried by spraying nitrogen (N2) gas, with a spray pressure of approximately 0.55 MPa and a spray speed of approximately 5 mm / s.
[0232] Subsequently, the dried precursor coating layer was heat-treated under the following conditions. First, a first heat treatment was performed for 5 minutes in an inline oven at 150°C, and a second heat treatment was performed for 5 minutes on a hot plate at 150°C. Finally, a third heat treatment was performed for 20 minutes on a hot plate at 100°C. Through the above process, a perovskite thin film having a thickness of approximately 700 nm was prepared.
[0233] Example 1b: Preparation of a perovskite thin film
[0234] A perovskite thin film was prepared by performing the same conditions as in Example 1a, except that the temperature of the first heat treatment performed in an inline oven was set to 170℃.
[0235] Comparative Example 1a: Preparation of a perovskite thin film
[0236] Except that formamidinium iodide (FAI) was not added to the precursor solution A perovskite thin film was prepared by performing the same conditions as in Example 1a.
[0237] Comparative Example 1b: Preparation of perovskite thin film
[0238] Except that formamidinium iodide (FAI) was not added to the precursor solution A perovskite thin film was prepared by performing the same conditions as in Example 1b.
[0239] Example 2: Fabrication of a photoelectric conversion device
[0240] A photoelectric conversion device was fabricated using the perovskite thin film prepared in Example 1b. A silicon underlay / TCO / HTL / SAM substrate was used as the substrate. The substrate surface was cleaned and activated by plasma treatment.
[0241] A self-assembled monolayer (SAM) was formed on an activated substrate. The perovskite precursor solution of Example 1b was applied thereon by a blade coating method, then dried by spraying an inert gas, and a perovskite thin film layer was formed by sequentially performing convective heat treatment and conductive heat treatment.
[0242] Lithium fluoride (LiF) and C60 layers were formed on top of the perovskite thin film by vacuum deposition. Then, a tin oxide (SnOx) layer was formed by atomic layer deposition (ALD). Next, an ITO layer was deposited by sputtering, and finally, a silver (Ag) electrode was formed by printing to complete the device.
[0243] Comparative Example 2: Fabrication of a photoelectric conversion device
[0244] A photoelectric conversion device was prepared by performing the same conditions as in Example 2, except that 2.5 mol% of formamidinium iodide (FAI) based on the molar amount of Pb was added to the precursor solution.
[0245] Comparative Example 3: Fabrication of a photoelectric conversion device
[0246] A photoelectric conversion device was prepared by performing the same conditions as in Example 2, except that 1 mol% of formamidinium iodide (FAI) based on the molar amount of Pb was added to the precursor solution.
[0247] Comparative Example 4: Fabrication of a photoelectric conversion device
[0248] A photoelectric conversion device was prepared by performing the same conditions as in Example 2, except that 7.5 mol% of formamidinium iodide (FAI) based on the molar amount of Pb was added to the precursor solution.
[0249] Experimental Example 1-1: XPS Composition Ratio Analysis
[0250] To confirm the composition ratio of the perovskite thin films prepared in Comparative Example 1a, Comparative Example 1b, Example 1a, and Example 1b, X-ray photoelectron spectroscopy (XPS) analysis was performed, and the results are shown in Table 1.
[0251] A / Pb X / Pb X / A A:Pb:X FA / Cs I / Br Comparative Example 1a 0.87 2.6 3.0 0.87:1:2.6 4.2 5.3 Comparative Example 1b 0.68 2.5 3.7 0.68:1:3.7 4.8 6.4 Example 1a 1.07 2.9 2.7 1.07:1:2.9 3.9 4.9 Example 1b 1.11 3.0 2.7 1.11:1:2.9 4.3 5.5 Theoretical value 1 3 3 1:1:3 4 4
[0252] As shown in Table 1, in Comparative Example 1a and Comparative Example 1b, the A / Pb ratios were 0.87 and 0.68, respectively, which were lower than the theoretical value (1.0). This is believed to be the result of some loss of highly volatile A-site cations during the film formation process due to the use of a precursor solution composed of stoichiometric ratios.
[0253] On the other hand, in Examples 1a and 1b, the A / Pb ratios were 1.07 and 1.11, respectively, which is interpreted as the result of compensating for compositional loss during the film formation process by setting the A-site cation concentration of the precursor solution to a non-stoichiometric excess. In addition, it was confirmed that the compositional uniformity was improved, as the FA / Cs ratio was close to the theoretical value (4) and the I / Br ratio was close to 4.
[0254] In addition, the A / Pb ratio in Example 1b, performed at 170°C, was closer to the theoretical value than in Example 1a, which was set to 150°C, and the deviation of the I / Br ratio was also reduced. This is attributed to the fact that residual solvent in the precursor was effectively removed by high-temperature heat treatment, and the uniformity of crystal growth was improved. Therefore, it was confirmed that high-quality perovskite thin films with a more uniform composition and improved crystallinity can be formed by combining a non-stoichiometrically designed precursor solution with high-temperature primary heat treatment conditions.
[0255] Experimental Example 1-2: XPS Composition Ratio Analysis
[0256] Additionally, X-ray photoelectron spectroscopy (XPS) analysis was performed to confirm the composition ratio of the perovskite thin films prepared in Comparative Example 2, Comparative Example 3, and Example 2, and the results are shown in Table 2.
[0257] A / Pb X / Pb X / A A:Pb:X FA / Cs I / Br Example 2 0.9 2.6 3.0 0.9:1:2.6 4.6 5.3 Comparative Example 2 0.5 2.3 4.5 0.5:1:2.3 5.3 7.5 Comparative Example 3 0.4 2.2 5.4 0.4:1:2.2 5.0 8.8 Theoretical value 1 3 3 1:1:3 4 4
[0258] As shown in Table 2, all three samples were designed with non-stoichiometric compositions by adding an excess amount of formamidinium iodide (FAI), but differences in compositional balance were observed depending on the amount added. In the case of Example 2 (FAI 5 mol%), the A / Pb ratio was approximately 0.9, which was closest to the theoretical value (1), while in Comparative Example 2 (FAI 2.5 mol%) and Comparative Example 3 (FAI 1 mol%), the ratios were approximately 0.5 and 0.4, respectively, indicating relatively lower compositional balance.
[0259] From these results, it was confirmed that when the excess amount of A-site cation added is at an appropriate level (e.g., about 5 mol% based on the molar amount of Pb), the reaction stability within the precursor is improved, which is advantageous for forming a perovskite thin film of uniform composition. In other words, when the A / Pb molar ratio is set in the range of 1.025:1 to 1.075:1, compositional non-uniformity during the film formation process is mitigated, which means that stable crystal growth can be induced.
[0260] Experimental Example 2: UPS Analysis
[0261] To determine the energy levels of the perovskite thin films prepared in Comparative Example 1b and Example 1b, Ultraviolet Photoelectron Spectroscopy (UPS) analysis was performed, and the results are shown in Fig. 8.
[0262] As shown in Fig. 8, in the case of Comparative Example 1b, the work function was measured to be approximately 5.26 eV, and the Fermi level was located at approximately 5.22 eV from the vacuum level. On the other hand, in the case of Example 1b, the work function increased to approximately 5.56 eV, and the conduction band and valence band were measured to be approximately 4.8 eV and 6.44 eV, respectively.
[0263] These results indicate that by non-stoichiometrically over-adjusting the A-site cations in the precursor solution, the electrically neutral state of the thin film approaches intrinsic semiconductor characteristics (intrinsic semiconductor state). Additionally, it can be confirmed that the charge transport barrier has been alleviated, as the energy difference between the conduction band of the electron transport layer and the valence band of the hole transport layer has decreased, and the energy difference between the conduction band and the hole transport layer has also decreased.
[0264] Therefore, it was confirmed that the non-stoichiometrically composed perovskite thin film forms an energy level alignment that facilitates charge extraction.
[0265] Experimental Example 3: XPS Chemical Bonding Analysis
[0266] To confirm the chemical bonding state of the perovskite thin films prepared in Comparative Example 1b and Example 1b, X-ray photoelectron spectroscopy (XPS) analysis was performed, and the results are shown in Fig. 9. Fig. 9 shows the O 1s and N 1s peaks for each sample.
[0267] In the O 1s spectrum of Fig. 9, a PbO peak and a peak attributed to residual solvent (NMP) were observed in Comparative Example 1b at around 531 eV. On the other hand, in Example 1b, these peaks were significantly reduced or disappeared, confirming that residual solvent in the thin film was effectively removed and PbO formation was suppressed by using a precursor solution with a non-stoichiometric composition.
[0268] Also, in the N 1s spectrum, Comparative Example 1b shows FA decomposition products or MA near approximately 398 eV. + While a peak corresponding to [the example] appeared, in Example 1b, a distinct peak corresponding to the FA bond was formed around 400 eV. This means that the Lewis base component in the precursor solution was successfully removed during the heat treatment process, and the FA was stably positioned within the lattice, thereby strengthening the bond.
[0269] Therefore, through this experimental example, it was confirmed that a precursor solution with a non-stoichiometric composition improves the bonding environment of the perovskite thin film and contributes to the formation of a high-purity crystalline phase.
[0270] Experimental Example 4: XRD Crystallinity Analysis
[0271] To confirm the crystal structure of the perovskite thin films prepared in Comparative Example 1b and Example 1b, X-ray diffraction (XRD) analysis was performed, and the results are shown in FIG. 10. FIG. 10 compares the diffraction peak intensities of the (110) plane and the (112) plane in each sample.
[0272] In the results of FIG. 10, the relative intensity of the (112) plane in both samples was similar, but in Example 1b, the diffraction intensity of the (110) plane relative to the (112) plane was 12.3 times, and in Comparative Example 1b, it was confirmed to be 8.8 times. Accordingly, it was confirmed that in the case of Example 1b, the diffraction intensity of the (110) plane increased significantly compared to the Comparative Example. This means that crystal growth occurred predominantly along the (110) crystal plane by using a precursor solution with a non-stoichiometric composition.
[0273] (110) Crystal planes are known to be crystal directions with low defect density, and this improvement in crystallinity can improve charge transport pathways within the thin film and reduce interfacial defects, thereby providing an effect of suppressing charge recombination. Therefore, it was confirmed that non-stoichiometric composition design contributes to vertical growth and improved crystal quality of perovskite crystals.
[0274] Experimental Example 5: Analysis of Photoelectric Conversion Efficiency (PCE)
[0275] The photoelectric conversion efficiency (PCE) of the silicon-perovskite tandem solar cells prepared in Comparative Example 2, Comparative Example 3, and Example 2 was measured, and the results are shown in FIGS. 11 and FIGS. 12.
[0276] As shown in Fig. 11, when the amount of formamidinium iodide (FAI) added to the precursor solution was 1 mol% (Comparative Example 3) and 2.5 mol% (Comparative Example 2), PCEs of approximately 23.10% and 22.85%, respectively, were observed, showing similar efficiencies. On the other hand, when the amount of FAI added was 5 mol% (Example 2), the PCE was improved to approximately 24.62%. This is considered to be the result of improved thin film quality due to the ensuring of uniformity in the precursor composition.
[0277] Meanwhile, as shown in Fig. 12, in the case of 7.5 mol% (Comparative Example 4), where the amount of FAI added was excessively high, the PCE decreased to approximately 18.97% as the insulating FAI remained and inhibited charge transfer. On the other hand, under the same process conditions, the highest efficiency was observed with a PCE of approximately 25.47% when the amount of FAI added was 5 mol% (Example 2).
[0278] From this, it was confirmed that a composition in which an A / Pb molar ratio of 1.025:1 to 1.075:1 was controlled by adding about 5 mol% of FAI based on the molar amount of Pb optimized the charge transport characteristics and photoelectric conversion efficiency of the perovskite thin film.
[0279] Experimental Example 6: Open-circuit voltage (Voc) analysis
[0280] The open-circuit voltage (Voc) of the silicon-perovskite tandem solar cells prepared in Comparative Example 2, Comparative Example 3, and Example 2 was measured, and the results are shown in FIG. 13.
[0281] As shown in Fig. 13, when the amount of formamidinium iodide (FAI) added to the precursor solution was 1 mol% (Comparative Example 3) and 2.5 mol% (Comparative Example 2), the Voc was approximately 1.759 V and approximately 1.771 V, respectively. On the other hand, when the amount of FAI added was 5 mol% (Example 2), the Voc increased to approximately 1.821 V.
[0282] These results are interpreted as a result of reducing defect density in the perovskite thin film and suppressing charge recombination loss by designing the composition of the precursor solution non-stoichiometrically. In particular, it was confirmed that a composition with an A / Pb molar ratio of 1.025:1 to 1.075:1, achieved by adding approximately 5 mol% of FAI based on the molar amount of Pb, improved the electrical quality of the perovskite layer and minimized Voc loss.
[0283] Experimental Example 7: Hysteresis Index (HI) Analysis
[0284] The hysteresis index (HI) of the silicon-perovskite tandem solar cells prepared in Comparative Example 2, Comparative Example 3, and Example 2 was measured, and the results are shown in FIG. 14.
[0285] As shown in Fig. 14, Comparative Example 2 and Comparative Example 3 exhibited HI values of approximately 12.06% and 11.58%, respectively, whereas Example 2 showed a low HI value of approximately 4.72%. This is interpreted as a result of using a precursor solution with a non-stoichiometric composition, which reduces defects and trap states within the perovskite thin film and suppresses charge accumulation phenomena occurring at the interface with the charge transport layer.
[0286] Therefore, it was confirmed that a composition with an A / Pb molar ratio of 1.025:1 to 1.075:1, created by adding approximately 5 mol% of FAI based on the molar amount of Pb, can ensure charge transfer uniformity, significantly reduce hysteresis phenomena, and improve device reliability through stable charge extraction.
[0287] The foregoing detailed description should not be interpreted restrictively in all respects but should be considered exemplary. The scope of the invention should be determined by a reasonable interpretation of the appended claims, and all modifications within the equivalent scope of the invention are included within the scope of the invention. Explanation of the symbols
[0288] 100: Photovoltaic conversion element 101: First electrode 102: Second electrode 110: Photoelectric conversion region 111: Electronic transport area 112: Precision Transport Area 113: Light absorption region 200: Multijunction photoelectric conversion device 201: First electrode 202: Second electrode 210: 1st subcell 220: 2nd subcell 230: Recombination region 250: n additional subcells and n additional recombination regions 300: Photovoltaic conversion module 310: First entry 320: Second entry 330: Multiple photoelectric conversion elements
Claims
Claim 1 A method for manufacturing a perovskite thin film comprising: a step of preparing a precursor solution comprising two or more different A-site cations, two or more different halide anions, and a B-site metal cation; a step of applying the precursor solution to a substrate to form a precursor coating layer; and a step of heat-treating the precursor coating layer to manufacture a perovskite thin film, wherein the sum of the moles of the two or more different A-site cations in the precursor solution is greater than the moles of the B-site metal cation. Claim 2 A method for manufacturing a perovskite thin film according to claim 1, wherein the molar ratio of the sum of the moles of two or more different A-site cations and the moles of the B-site metal cations in the precursor solution is 1.025:1 to 1.075:
1. Claim 3 In claim 1, the two or more different types of A-site cations include a first A-site cation and a second A-site cation, and the first A-site cation is methylammonium (CH3NH3 + , MA + ), formamidinium (HC(NH2)2 + , FA + ), and ethylammonium (CH3CH2NH3 + , EA + It comprises one or more organic cations selected from the group consisting of ), and the second A-site cation is Cs + , Rb + , Cu + , Pd + , Pt + , Ag + , Au + , Rh + , and Ru + A method for manufacturing a perovskite thin film comprising one or more inorganic cations selected from the group consisting of Claim 4 A method for manufacturing a perovskite thin film according to claim 3, wherein the molar ratio of the first A-site cation and the B-site metal cation is 0.825:1 to 0.875:
1. Claim 5 A method for manufacturing a perovskite thin film according to claim 1, wherein the molar ratio of the sum of the moles of two or more different halide anions and the moles of the B-site metal cation in the precursor solution is 3.025:1 to 3.075:
1. Claim 6 A method for manufacturing a perovskite thin film according to claim 1, wherein the two or more different halide anions include a first halide anion and a second halide anion, and the molar ratio of the first halide anion to the B-site metal cation is 2.425:1 to 2.475:
1. Claim 7 A method for manufacturing a perovskite thin film according to claim 1, wherein the precursor solution further comprises an additive, and the additive comprises a monovalent alkylammonium halide. Claim 8 A method for manufacturing a perovskite thin film according to claim 7, wherein the precursor solution comprises 20 mol% to 30 mol% of the additive based on the molar amount of the B-site metal cation. Claim 9 A method for manufacturing a perovskite thin film according to claim 1, wherein the precursor coating layer is formed by a blade coating method. Claim 10 A method for manufacturing a perovskite thin film according to claim 1, wherein the precursor coating layer is dried using an inert gas sprayed at a pressure of 0.3 MPa to 0.7 MPa. Claim 11 A method for manufacturing a perovskite thin film according to claim 1, wherein the heat treatment comprises a first heat treatment step performed at a temperature of 120°C to 200°C; and a second heat treatment step performed at a temperature of 50°C to 170°C. Claim 12 A method for manufacturing a perovskite thin film according to claim 11, wherein the first heat treatment step is performed by convection heat treatment and the second heat treatment step is performed by conduction heat treatment. Claim 13 A method for manufacturing a perovskite thin film according to claim 11, wherein the first heat treatment step is performed for 1 minute to 30 minutes and the second heat treatment step is performed for 5 minutes to 120 minutes. Claim 14 A method for manufacturing a perovskite thin film according to claim 1, wherein the thickness of the perovskite thin film is 500 nm to 800 nm. Claim 15 A method for manufacturing a perovskite thin film according to claim 1, wherein the perovskite thin film has a composition represented by the following chemical formula 1: [Chemical Formula 1]FA 1-x Cs x Pb(I 1-y Br y )3 The above x is a real number from 0.1 to 0.3, and the above y is a real number from 0.1 to 0.
3. Claim 16 A method for manufacturing a perovskite thin film according to claim 1, wherein the band gap of the perovskite thin film is 1.60 eV to 1.90 eV. Claim 17 Perovskite thin film manufactured according to claim 1. Claim 18 A photoelectric conversion device comprising the perovskite thin film of claim 17.
Citation Information
Patent Citations
Precursor for Perovskite Compound and the Fabrication Method of Perovskite Compound Using Thereof
KR1020210126210A
Method and apparatus for manufacturing metal halide perovskite quantum dot having enhanced stability, and solar cell comprising the metal halide perovskite quantum dot manufactured thereby
KR1020230068982A
Perovskite precursor solution based green-solvent and fabrication method of perovskite thin film using the same
KR1020230156478A
A method for producing a semiconducting film of organic-inorganic metal-halide compound with perovskite-like structure
KR1020240135073A
